Phosphorus and carbon solubilization strategies for wastewater sludge valorisation. Issue 5 (October 2021) - Kolakovic, Srdana; Santos, Jorge M.M.; Reis, Maria A.M.
Abstract: Phosphorus and carbon solubilisation from wastewater sludges is a difficult task due to specific sludge characteristics and low biodegradability of sludges. This work evaluates operational strategies to solubilise phosphorus and/or carbon from different municipal sludges in a bioacidification reactor operated at low sludge retention time (SRT) compared to conventional digestors, with the objective of valorising sludge and recovering resources onsite of a water resource recovery facility (WRRF). The individual impact of three municipal sludges, three organic loading rates (OLR), two SRTs, two temperatures and thermal hydrolysis pre-treatment was assessed through a well-designed experimental methodology. Bioacidification provided a maximum 79% of PO4 3- -P/Ptot and 29% of CODsol /CODtot solubilisation ratios, which was an increase of approximately 60% and 26%, respectively, compared to a non bioacidified sludge. Similar performance was achieved for the three different sludges and OLRs used in this study under SRT of 4 days and 35 °C. Kinetic tests elucidated that lower SRT (2 days) and temperature (20 °C) negatively impacted P release due to biological fermentation decrease. Iron and polyphosphate release was impacted by present microbial community, while calcium release was more dependent on pH. Organic phosphorus, nitrogen and carbon solubilisation was limited by low sludge hydrolysis and increased only after a thermal-alkaline sludge hydrolysis pre-treatment (pH 9, 80 °C for 1 h) was combined with the bioacidification. This study demonstrates the high potential of the bioacidification process to valorise sludge and provides recommendations for its implementation onsite based on the individual requirements of each WRRF. Graphical Abstract: ga1 Highlights: Semi-continuous bioacidification at low SRT showed high potential for P release. Testing various sludges and conditions elucidated the release of each P fraction. Bioacidification treatment is required to reach high PO4 3- -P/Ptot ratios (60–73%). Adding batch thermal hydrolysis increased P (+ 10.0%) and C (+ 16.0%) solubilisation. Combining thermal hydrolysis and bioacidification increased VFA production 2–2.8 ×.